Outcomes of a Standardized Protocol on the Management of Acute Type A Aortic Dissection: A Retrospective Cohort Study - Philippoz, Supitchaya; Adamopoulos, Dionysios; Sologashvili, Tornike; Steenberghe, Mathieu van; Jolou, Jalal; Huber, Christoph; Cikirikcioglu, Mustafa (AORTA, 2024)
Acute Type A aortic dissection (AAAD) is a life-threatening condition, with surgery being the recommended treatment. However, there is ongoing debate regarding the optimal surgical procedure. This study aimed to evaluate the impact of implementing a standardized protocol, introduced in our institution in 2016, on AAAD management.A retrospective cohort study was conducted involving patients treated surgically for AAAD between 2010 and 2021 in our department. Patients were divided into two groups: those who underwent surgery before 2016 using operator-dependent techniques, and those who underwent surgery starting in 2016 using a standardized protocol.A total of 104 patients were included in this study. The mean age was 66.5 ± 11.4 years and 55.8% were male. Demographics and preoperative data were similar in both groups. Arterial and venous cannulation site of both groups were different (p < 0.001): femoral artery and vein cannulation for group 1 versus subclavian artery and central venous canulation for group 2. Alone ascending aorta replacement versus ascending aorta plus hemiarch replacement were the preferred techniques in groups 1 and 2, respectively (p < 0.001). Hypothermic circulatory arrest and cerebral perfusion were largely performed in group 2 compared with group 1 (p < 0.001). The total time of surgery, the cardiopulmonary bypass, and aortic cross-clamping times were longer in group 2 (p < 0.05). Both groups had similar rates of postoperative complications, except for late reoperation and aortic dilatation rates, which were less frequent in group 2 (p < 0.05).The implementation of a standardized institutional protocol can transform AAAD surgery from a “surgeon-tailored” to a “ patient-tailored” approach. The use of a standardized protocol in our institution resulted in a significant reduction of aortic reoperation and aortic dilation rates, suggesting that the introduction of standardized protocols in low-volume centers may improve AAAD management.
Keywords: acute Type A aortic dissection; aortic surgery; acute aortic syndrome